Participation of TKM Caring for The Elderly in Carrying Out Social Services in Kertaharja Village Sumedang Regency - Rosilawati Rosilawati (Politeknik Kesejahteraan Sosial Bandung, 2023)
Participation is a central concept and basic principle of community development. This is based on the linkage of participation with many things, especially with the idea of human rights, thus making participation a concept that has the aim of activating ideas, the right to participate in democracy, strengthening liberative democracy and as a process of community development. On this basis, TKM that has been formed has the right to actively contribute to social service activities for the elderly. The participation of TKM Cares for the Elderly